646. Activated Macrophages as Pathogenesis Factors in Ebola Virus Disease in Humans. (26th November 2018) - McElroy, Anita; Shrivastava-Ranjan, Punya; Harmon, Jessica; Martines, Roosecelis; Silva-Flannery, Luciana; Flietstra, Timothy; Kraft, Colleen; Mehta, Aneesh K; III, G Marshall Lyon; Varkey, Jay; Ribner, Bruce; Nichol, Stuart; et al.
Abstract: Background: Ebola virus disease (EVD) is associated with elevated cytokine levels that are more pronounced in fatal cases. This type of hyperinflammatory state is reminiscent of other inflammatory disorders, such as macrophage activation syndrome (MAS) or hemophagocytic lymphohistiocytosis (HLH). These are both part of a spectrum of rheumatologic phenomena characterized by both macrophage and T-cell activation. These disorders can be secondary to infection, malignancy, underlying rheumatologic disorder, or, paradoxically, immune deficiency. Methods: Two cohorts of EVD patients were evaluated with respect to common plasma markers of HLH/MAS. Immunohistochemistry was used to evaluate tissue macrophages and viral antigens in various tissues from fatal cases of EVD. Results: Neither fibrinogen nor soluble IL-2 receptor were significantly different between fatal and nonfatal cases. However, elevated levels of triglycerides, ferritin and sCD163, a marker of macrophage activation were noted in patients with EVD and they correlated with disease severity and a fatal outcome. Furthermore, significant immunoreactivity for CD163 + cells in host tissues was observed in fatal cases, predominantly in areas of extensive immunostaining for EBOV antigens. Conclusion: These data suggest that host macrophage activation contributes to EVD pathogenesis and that directed anti-inflammatory therapies could be beneficial in the treatment of EVD. Disclosures: All authors: No reported disclosures.